Plunging wave impact on a wall - Shu, Jian Jun (2011)
The intention of this paper is to study impact force of an oblique-angled slamming wave acting on a rigid wall. In the present study the analytical approach is pursued based on a technique proposed by the author. A nonlinear theory in the context of potential flow is presented for determining accurately the free-surface profiles immediately after an oblique breaking wave impingement on the rigid vertical wall that suddenly starts from rest. The small-time expansion is taken as far as necessary to include the accelerating effect. The analytical solutions for the free-surface elevation are derived up to the third order. The results derived in this paper are of particular interest to the marine and offshore engineering industries, which will find the